Androgen receptor decoy molecules block the growth of prostate cancer - Quayle, Steven N. (National Academy of Sciences, 2007)
The androgen receptor (AR) is activated by both ligand-dependent and -independent mechanisms. Current therapies for prostate cancer target the ligand-binding domain in the C terminus of the AR. However, ligand-independent activation of the AR occurs by the N-terminal domain (NTD), making the NTD a potential novel target for the treatment of hormone refractory prostate cancer. A possible therapeutic approach is to overexpress an AR NTD peptide to create decoy molecules that competitively bind the interacting proteins required for activation of the endogenous full-length AR. We provide evidence that in vivo expression of AR NTD decoys decreased tumor incidence and inhibited the growth of prostate cancer tumors. This growth inhibition was characterized by a 10-fold decrease in serum levels of prostate-specific antigen (PSA) (46.7 ng/ml ± 19.9 vs. 432.4 ng/ml ± 201.3; P = 0.0299) and a 4-fold decrease in tumor volume (92.2 mm(3) ± 43.4 vs. 331.4 mm(3) ± 85.5; P = 0.011). AR NTD decoy molecules also delayed hormonal progression, as determined by time to rising PSA levels after castration of the host. The tumors treated with AR NTD decoys contained more apoptotic cells and fewer proliferating cells, whereas no effect was seen on the viability of cells that did not depend on the AR. This work provides further evidence of the importance of the NTD of the AR in the progression of prostate cancer and presents a target for the development of antagonists of the AR in the clinical management of this disease.